Regional Economic Outlook, October 2019, Western Hemisphere Department. (Regional Economic Outlook, 2019)
The global economy has slowed, with important consequences for growth prospects in Latin America and the Caribbean. The slowdown in economic activity has been broad-based among advanced economies and more pronounced in emerging markets and developing economies, partly reflecting trade and geopolitical tensions. Global growth is projected to decline to the lowest level since the global financial crises, before recovering in 2020. More importantly, growth is projected to decline in 2019-20 in the United States and China, which are LAC's two main trading partners. The ongoing sluggishness of global growth and trade is affecting export growth in LAC, posing significant headwinds to the outlook. External demand for the region remains subdued, with trading partner growth (including China, Europe, other LAC countries, and the United States) projected to decline in 2019, before recovering modestly over the medium term. Moreover, commodity prices (notably energy and metals), key drivers of growth in LAC in the past, are projected to decline with a likely modest negative impact on regional growth going forward.